Multifunctional "Smart" Particles Engineered from Live Immunocytes: Toward Capture and Release of Cancer Cells. (10th November 2014) - Huang, Chao; Yang, Gao; Ha, Qing; Meng, Jinxin; Wang, Shutao
<x xml:space="preserve">Abstract</x> Multifunctional "smart" particles with magnetic, topographic, cell‐targeting, and stimulus‐responsive properties are obtained using a "live template" strategy. These particles exhibit improved efficiency in capture of target cancer cells by introducing synergistic topographic interactions, and enable the release of captured cells with high viability via reduction of disulfide bonds. Diverse multifunctional particles can be designed using the "live template" strategy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>